A Critical Review of Ground Based Observations of Earthquake Precursors - Conti, Livio; Picozza, Piergiorgio; Sotgiu, Alessandro (Frontiers in Earth Science, 2021)
We aim at giving a short review of the seismo-associated phenomena detected on ground that in recent years have been investigated as possible earthquake precursors. The paper comes together with a companion article - published on this same volume by Picozza et al. 2021 - devoted to summarize the space-based observation of earthquake-precursors by satellites missions. In the present work, we give an overview of the observations carried out on ground in order to identify earthquake precursors by distinguishing them from the large background constituted by both natural non-seismic and artificial sources. We start discussing the measurements of mechanical parameters and variations of geochemical fluids detected before earthquakes; then we review thermal and atmospheric oscillations; finally, observations of electromagnetic and ionospheric parameters possibly related to the occurrence of impeding earthquakes are discussed. In order to introduce a so large field of research, we focus only on some main case studies and statistical analyses together with the main hypotheses and models proposed in literature in order to explain the observed phenomenology.